PENGARUH PROSES PENGOLAHAN EKADO TERHADAP KOMPOSISI GIZI IKAN TONGKOL BERDASARKAN ANALISIS PROKSIMAT (PROTEIN, LEMAK, KARBOHIDRAT, AIR, DAN ABU) - Nadia Nadia; Nurhaifa Nurhaifa; Ridho Ridho; Thera Simartama (PPPM POLTESA, 2026)
Ekado mackerel tuna is an innovation in the processing of mackerel tuna, developed with the aim of achieving good nutritional value and adequate shelf life. Mackerel tuna itself is recognized as a raw material for processed products with high nutritional content, particularly in terms of protein. This study aims to evaluate the nutritional composition of ekado mackerel tuna through proximate analysis, which includes protein, fat, carbohydrates, moisture, and ash content. The analytical methods applied involve determining moisture content using the oven method, ash content through ashing, protein content via the Kjeldahl method, fat content by Soxhlet extraction, and carbohydrate content calculated by difference. The research findings reveal that ekado mackerel tuna has a relatively high protein content, with balanced levels of fat and carbohydrates. Furthermore, its moisture and ash contents still meet the applicable quality standards for processed fish products. This nutritional profile indicates that the product has the potential to become a nutritious processed fish item and is worthy of further development. Through this study, it is expected to provide scientific information regarding the product's nutritional content, while also encouraging the advancement of value-added processed mackerel tuna products.